Z-Scheme g-C3N4/Bi4NbO8Cl Heterojunction for Enhanced Photocatalytic Hydrogen Production - You, Y.; Wang, Shaobin; Xiao, K.; Ma, T.; Zhang, Y.; Huang, H. (American Chemical Society, 2018)
Photocatalytic water splitting is promising for sustainable energy development, but it is severely challenged by the low charge separation efficiency and slashing redox potentials requirement. Fabricating a Z-scheme heterojunction as an effective strategy for solving the aforementioned troubles gains enormous efforts. In this work, we develop high-efficiency Z-scheme catalyst g-C3N4/Bi4NbO8Cl based on a facile high-energy ball-milling method to form an intimate interface between the two phases. It exhibits an enormously promoted photocatalytic activity for H2 production with visible-light illumination (λ > 420 nm), and the H2 evolution rate is 6.9 and 67.2 times higher than those of bare g-C3N4 and Bi4NbO8Cl, respectively. The stronger photoabsorption of g-C3N4/Bi4NbO8Cl (beyond 500 nm) allows generation of more photons than does g-C3N4. More importantly, the separation and transfer of photoexcited charge carriers were greatly improved between g-C3N4 and Bi4NbO8Cl, as revealed by the photoelectrochemical and time-resolved photoluminescence decay results. The Z-scheme charge transfer mechanism of g-C3N4/Bi4NbO8Cl was also manifested by electron spin resonance (ESR). The work furnishes a new solution to fabrication of high-efficiency Z-scheme catalysts for countering energy issues.